Cone Beam Computed Tomography (CBCT) Evaluation of Age-related Upper Airway Changes (Bangladesh Journal of Medical Science, 2016)
Background: Upper airway morphology is associated with facial development and occlusion. Treatment of maxillofacial and occlusal disorders requires sufficient knowledge of related functional variables, including upper airway morphology. In order to determine upper airway obstruction and its exact site, three-dimensional (3D) reconstruction of the airway can be beneficial. The aim of the current study was to determine the age-related changes of upper airway morphology.Materials: The pharyngeal area of 87 patients was assessed using Cone Beam Computed Tomography (CBCT), and no artifacts were detected. The subjects were within the age range of 6-60 years, with normal body mass index (BMI) of 18-25 kg/m2. In the CBCTs, in addition to volumetric measurements of nasopharynx, oropharynx, and hypopharynx, distances between pharyngeal wall and posterior nasal spine, uvula, or valcula in anteroposterior and horizontal planes were measured (2D measurement). In addition, the shortest distance between tongue base and posterior pharyngeal wall was calculated in the anteroposterior plane. Data were analyzed in three age groups of 6-20, 21-40, and 41-60 years old via SPSS analysis.Results: Various values of upper airway and variables which measure anteroposterior dimensions of pharynx were significantly higher in the 21-40 years old group, compared to 6-20 years old group. Although these variables were higher in the 21-40 years old group, compared to the 41-60 years old group, the difference was statistically insignificant. The transverse variables had the highest value in the 21-40 years old group, but the difference with the other two groups was insignificant. No significant difference was observed between males and females.Conclusion: According to the results of the current study, upper airway changes in 2D and 3D models may be age-dependent and become more significant by the age of 20 years. In addition, gender has no effect on the development of upper airways.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.78-83